3D (micro/nano) CdO/p-Si co-doped Zn and La heterojunctions perform as solar light photodetectors - Gozeh, Bestoon Anwer; Slewa, Lary H.; Ismael, Cheman Baker; Saleh, Sarwar Ibrahim; Yildiz, Abdulkadir; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2025)
Cadmium oxide is among the most appealing materials since it may be utilized in a variety of applications, including photodetector. Al/La-Zn/co-doped CdO/p-type Si/Al photodetectors were fabricated using the sol-gel spin coat technique, with the CdO interface layer, varying concentrations of La (0.1, 0.5, 2, and 4 at%), and constant Zn (1 at%). Each film was grown on glass and silicon substrates so that their optical and electrical properties could be evaluated. Analyses were conducted on the morphological, optical, and electrical properties of transparent, co-doped CdO photodetectors. Using a field emission scanning electron microscope and energy dispersive X-ray, the morphological properties and elemental compositions of prepared materials The FESEM images revealed a 3-D micro/nanostructure of La/Zn-co-CdO form, characterized by the formation of microspheres by the use of nanoneedles. Additionally, the development rate of the films was observed to be inhibited by the co-doping of CdO with La-Zn. The transmittance measurements show that the prepared films exhibit a ranging from 40 to 70 % in the visible spectrum. The optical bandgap of prepared thin films measured by linear fitting where increases linearly with increasing La-Zn co-dopant concentration and was found in range between (2.07 and 2.27 eV). When CdO was co-doped with La (0.1 at%) and Zn (1 at%), the I-V properties of the produced photodetectors revealed high rectifying behavior. The photovoltaic and photoelectrical behaviors are shown, together with associated parameters. Additionally, the dopant concentration of (La 0.1 and Zn 1) at% has the highest photoresponse behavior at about 4085, surpassing findings in prior research. The highest photosensitivity of 6.3 x 10-4 has been determined for La 0.1 and Zn 1) at%. The strong rectifying characteristics, together with the photovoltaic, photoelectrical, and photoresponse properties, indicate that the fabricated (La 0.1 and Zn 1) at% co-doped CdO-based photodetector is suitable for optoelectronic applications, particularly in sensors and photodetectors.
Keywords: Sol-gel method; Optical and electrical properties; Photodetector; Photoresponse